Efeitos tardios de correr uma meia-maratona sobre a cinemática de corredores - Carvalho, Jean da Silva (2023)
High-intensity efforts involving eccentric muscle actions are common source of delayed-onset muscle soreness (DOMS). A DOMS condition can impair, even in a transitory way, force production, range of motion, muscle and joint stiffness, and comfort during movement performance. In runners, these effects could alter running kinematics, impairing performance, and/or increasing the presence of risk factors for injuries. Since regenerative training sessions are common on days following a high-intensity effort. In this study, we investigate whether there are delayed effects of a simulated half-marathon competition on the threedimensional (3D) running kinematics. The study included 15 runners (11 men, 4 women) with competitive experience and mean ± standard deviation age of 36 years ± 9 years old. They ran a half-marathon to achieve their personal best time. Pre and post the running they were submitted to evaluations involving anamnesis about sports practice, anthropometric measurements, responses to effort scales, perceived recovery, pressure pain threshold, and a 3D kinematic evaluation of running on a treadmill. During the half-marathon, relative air humidity and wind speed, total distance, elevation, finish time, speed, effort perception and heart rate were monitored. According to our results, we interpret that the demand for high-intensity exercise in a half-marathon causes muscle damage, reflected in the presence of delayed muscle soreness, evidenced by the greater sensitivity noted in the pain thresholds due to pressure in musculature. Regarding the 3D running kinematics, we observed that after the half-marathon, some pre-existing characteristics in the running technique are accentuated, such as asymmetries in the lower limbs, greater range of motion and asymmetry in trunk movement and longer contact times. In conclusion, after running a half-marathon and experiencing DOMS indicating muscle damage, runners change their running technique some movement profiles that might indicate negative effects on performance and injury risk factors can be accentuated.